Comorbidities in Obsessive-Compulsive Disorder Across the Lifespan: A Systematic Review and Meta-Analysis - Sharma, Eesha; Sharma, Lavanya P.; Balachander, Srinivas; Lin, Boyee; Manohar, Harshini; Khanna, Puneet; Lu, Cynthia; Garg, Kabir; Thomas, Tony Lazar; Au, Anthony Chun Lam; Selles, Robert R.; Højgaard, Davíð R. M. A.; et al. (Frontiers in Psychiatry, 2021)
Comorbidities are seen with obsessive-compulsive disorder (OCD) across the lifespan. Neurodevelopmental comorbidities are common in young children, followed by mood, anxiety, and obsessive-compulsive related disorders (OCRDs) in children, adolescents and adults, and neurological and degenerative disorders in the elderly. Understanding comorbidity prevalence and patterns has clinical and research implications. We conducted a systematic review and meta-analysis on comorbidities in OCD across the lifespan, with the objective to, first, estimate age-wise pattern and prevalence of comorbidities with OCD and, second, to examine associations of demographic (age at assessment, gender distribution) and clinical characteristics (age of onset, illness severity) with comorbidities. Four electronic databases (PubMed, EMBASE, SCOPUS and PsycINFO) were searched using predefined search terms for articles published between 1979-2020. Eligible studies, across age, reported original findings on comorbidities and had an OCD sample size of >/=100. We excluded studies that did not use standardized diagnostic assessments, or that excluded patients on the basis of comorbidity. We adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The review protocol has been registered on the International Prospective Register of Systematic Reviews. A comorbidity rate of 69% was found in a pooled sample of more than 15000 individuals. Mood disorders (major depressive disorder), anxiety disorders (generalized anxiety disorder), neurodevelopmental disorders (NDDs) and OCRDs were the commonest comorbidities. Anxiety disorders prevailed in children, mood disorders in adults, whereas NDDs were similarly prevalent. Higher comorbidity with any psychiatric illness, NDDs, and severe mental disorders was seen in males, versus females. Illness severity was inversely associated with rates for panic disorder, tic disorders, OCRDs, obsessive compulsive personality disorder, and anorexia nervosa. This systematic review and meta-analysis provides base rates for comorbidities in OCD across the lifespan. This has implications for comprehensive clinical evaluation and management planning. The high variability in comorbidity rates suggests the need for quality, multi-centric, large studies, using prospective designs .